2014
DOI: 10.1002/psc.2732
|View full text |Cite
|
Sign up to set email alerts
|

Design of antimicrobial peptide arenicin analogs with improved therapeutic indices

Abstract: β-Hairpin antimicrobial peptides are among the most potent peptide antibiotics of animal origin. Arenicins, isolated earlier from marine polychaeta lugworm Arenicola marina, belong to a family of β-hairpin antimicrobial peptides and display a broad spectrum of biological activities. However, despite being potent antimicrobials, arenicins are partially unapplicable as therapeutics as a result of their relatively high cytotoxicity against mammalian cells. In this study, a template-based approach was used to crea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 50 publications
(63 citation statements)
references
References 31 publications
2
58
0
3
Order By: Relevance
“…Recombinant arenicin-1 and tachyplezin-1 were obtained by heterologous expression in E. coli cells [9,10]. For antibiotic activity assessment, bacterial strains E. coli C600, S. aureus 209P and P. aeruginosa PAO1 were used as test cultures.…”
Section: Methodsmentioning
confidence: 99%
“…Recombinant arenicin-1 and tachyplezin-1 were obtained by heterologous expression in E. coli cells [9,10]. For antibiotic activity assessment, bacterial strains E. coli C600, S. aureus 209P and P. aeruginosa PAO1 were used as test cultures.…”
Section: Methodsmentioning
confidence: 99%
“…The recombinant arenicin-1 and its mutant analogs were prepared as described previously [9]. 15 were induced with 0.2 mM IPTG.…”
Section: Peptidesmentioning
confidence: 99%
“…Vice versa, the analogs with low antimicrobial activity and pronounced hemolytic properties were found suggesting different mechanisms of the peptide action against pro-and eukaryotic cells. Interestingly, substitutions of the N-terminal β-strand aliphatic residues for the basic side chain amino acid arginine (Val4Arg, Ala6Arg, or Val8Arg) resulted in the most notable decrease in hemolytic activity [9]. The CD spectroscopy demonstrated that secondary structures of the analogs were quite similar in water and DPC micelles in contrast to the wildtype arenicin-1.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Initially, the expression and purification scheme, described in details in our previous work [5], was used to obtain recombinant THI. Briefly, induction of log-phase cells grown in LB media was performed by IPTG at 30…”
Section: Recombinant Thi Expression and Purificationmentioning
confidence: 99%